2011
DOI: 10.1111/j.1530-0277.2010.01380.x
|View full text |Cite
|
Sign up to set email alerts
|

The Limbic-Hypothalamic-Pituitary-Adrenal Axis and the Development of Alcohol Use Disorders in Youth

Abstract: Objective-As the initiation and acceleration of alcohol use commonly occurs during adolescence, the etiological basis for this phenomenon is of critical importance. Using the diathesis-stress model as a framework, this review will evaluate the emerging evidence implicating the limbic-hypothalamic-pituitary-adrenal (LHPA) axis in the development of alcohol use disorder (AUD).Method-Searches were conducted of the PubMed/Medline, PsycInfo, PsycBooks, Cochrane and ISI Web of Science databases, using a specified se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 154 publications
(201 reference statements)
1
32
0
2
Order By: Relevance
“…According to several neurobiological models (e.g., Koob and Le Moal, 2008;Schepis et al, 2011), dysregulation of the brain's stress/anxiety systems caused by repeated episodes of substance use and withdrawal underlies the development of substance dependence. Because the same brain systems are dysregulated in those with anxiety disorders even before any drug or alcohol use (Holsboer, 1989;LeDoux, 2007;Pervanidou, 2008;Van den Bergh et al, 2008), we theorized that the development of substance dependence should be more effi cient and, therefore, accelerated in this group (dependence susceptibility).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several neurobiological models (e.g., Koob and Le Moal, 2008;Schepis et al, 2011), dysregulation of the brain's stress/anxiety systems caused by repeated episodes of substance use and withdrawal underlies the development of substance dependence. Because the same brain systems are dysregulated in those with anxiety disorders even before any drug or alcohol use (Holsboer, 1989;LeDoux, 2007;Pervanidou, 2008;Van den Bergh et al, 2008), we theorized that the development of substance dependence should be more effi cient and, therefore, accelerated in this group (dependence susceptibility).…”
Section: Discussionmentioning
confidence: 99%
“…We extrapolated this idea, in part, from the work of George Koob and others who point to dysregulation in the brain's stress/anxiety systems (e.g., the extended amygdala and hypothalamic-pituitary-adrenal axis) resulting from chronic substance use as a core process ("allostasis") in the development of physical dependence (e.g., Koob, 2003;Koob and Le Moal, 2008;Schepis et al, 2011). Considering the neurobiological dysregulations associated alcoholinduced allostasis and the dysregulations in these same brain systems identifi ed as neurobiological hallmarks of anxiety disorders (Holsboer, 1989;LeDoux, 2007;Pervanidou, 2008;Van den Bergh et al, 2008), we hypothesized that the neuro-patho-developmental processes leading to dependence should be more effi cient, and therefore accelerated, in those with an anxiety disorder.…”
mentioning
confidence: 99%
“…In the second experiment, we investigated the effect of adolescent chronic EtOH on long‐lasting changes in the adult stress response to determine persistence of potential stress–alcohol interactions. In humans, adolescent stress, trauma, and binge drinking have been hypothesized to contribute to persistent dysfunctional HPA responses that increase risks of AUD (Schepis et al., 2011). We studied a rat adolescent intermittent EtOH (AIE) model that has been shown to cause a persistent increase adult brain neuroimmune signaling cytokines and chemokines to determine whether there were persistent changes in microglial or neuronal responses to stress (Crews and Vetreno, 2016; Vetreno and Crews, 2012; Vetreno et al., 2013).…”
mentioning
confidence: 99%
“…Some studies suggest that HPA axis dysfunction is a risk factor for future alcohol use disorders (Schepis et al 2011; Sher 2007), while other studies found that alcoholics with attenuated stress responses were more likely to relapse (Clapp et al 2008; Obara et al 2009). Combined with data showing increased adrenal weight in the ethanol treated subjects, these data suggest that chronic treatment may act as a physiological stressor.…”
Section: Discussionmentioning
confidence: 99%